Peripartum Cardiomyopathy: A Case Report - Firman; Akmal Mufriadi Hanif (HM Publisher, 2024)
Background: Peripartum cardiomyopathy (PPCM) is a type of dilated cardiomyopathy of unknown origin. Predisposing factors for PPCM are multiparity, family history, ethnicity, smoking, diabetes, hypertension, preeclampsia, malnutrition, and advanced age in pregnant women or teenage pregnancy. Case presentation: A 29-year-old female patient was treated in the internal medicine department of Dr. M. Djamil General Hospital Padang on March 18th, 2023, with the main complaint of shortness of breath. On physical examination, signs of congestion were found. ECG shows sinus tachycardia, QT prolongation, and T inversion in V3-V6, II, III, and aVF. The patient is established with peripartum cardiomyopathy, community-acquired pneumonia, nonsevere low-risk MDR, hypochromic microcytic mild anemia et causa chronic disease, high-risk VTE, h hypokalemia et causa diuretic. Conclusion: Education regarding recurrent recurrence of PPCM in subsequent pregnancies is 30-50%. The prognosis depends on the recovery of left ventricular function; 30% of patients can return to baseline ventricular function within 6 months, and 50% of patients have an improvement in symptoms and ventricular function. Contraception is recommended that does not pose a risk of thromboembolism, such as a uterine device (IUD) and subcutaneous progesterone.